(untitled) (Bangladesh Pharmaceutical Journal, 2020)
Physiological problems due to deficiency of minerals and vitamins level in Bangladeshi female population are on the rise. The primary goal of this study was to find out the intake of nutritional supplements among urban female population. A survey on nutritional supplements was designed for females in some selected area of Dhaka city. One hundred fifty females were recruited, segmented under two sections (non-pregnant / pregnant) and most of them were interviewed face-to-face systematically. 10.7% of the sample was pregnant women and the rest (89.3%) was the non-pregnant category. Participants were asked questions about their prescription drug patterns and intake of nutritional supplements. The study revealed that 53.0% of the female patients were not aware of the value of daily intake of nutritional foods. So, we also found that nutritional supplements were given to the patients continuously (34.48%), occasionally (18.39%) and at first (28.74%). Calcium supplement (36.90%), zinc supplement (14.10 %) and iron supplement (19.90 %) were prescribed most. Bangladesh Pharmaceutical Journal 23(1): 39-43, 2020